Penyakit Paru Obstruktif Kronis (PPOK) dengan Multipel Komorbid - Bowo Adiyanto; Maryani, Nova; Akhmad Yun Jufan (Jurnal Komplikasi Anestesi, 2023)
Background: COPD is a common disease, can prevent and cure, but sometimes its difficult to diagnose and misdiagnose. Hence, patient couldn’t have the correct treatment. Case: A man 76 years old transfer from district hospital with diagnose COPD with multiple comorbid such as CAP, AKI, and CHF cf III needs to hemodialysis. One month before hospitalization, patient complaint dyspnea and become worst in last 1 week. The quality of dyspnea increasing by activity and cough. Cough with white sputum. He has intubated and give treatment for COPD and other comorbids. Patient hospitalize in ICU for 12 days and after that transfer to HCU for further treatment. Discussion: Intubation and weaning process for COPD patient was very challenging. Patient has treatment 12 days in ICU have COPD medical support based on diagnosa and management ventilation with NIV and NRM after autoextubate on day 5. Clinical and imaging evaluation shows us the recovery of pneumonia and pulmo edema that’s help patient to breathing easily even COPD needs more times to resolve. Results: COPD with multiple comorbid disease make the intesivist more difficult to wean and manage the treatment. Keywords: COPD, Cor Pulmonale, ICU